Buckling of Hyperbolic Paraboloids - Buchert, Kenneth P. (Engineering Journal, 1972)
Large spherical dome roofs are being constructed regularly because of their beauty, adaptability, and low cost. A decade ago this type of roof was rather rare because of the high cost of construction and the significant unknowns in the design. Considerable research and development in design and construction has resulted in analysis procedures that have a high degree of reliability and are carried out at minimum cost (often the dome analysis is much more economical than the analysis of a similar size conventional type structure.) Ingenious fabrication and erection methods have paralleled the analysis development with resulting relatively low final costs. Designs have been carried to completion for roofs up to 850 ft in base diameter (the Astrodome is about 620 ft in base diameter). Preliminary feasibility designs have been made for roofs over one mile in diameter. The buckling analysis is an important part of dome design. Several large domes have failed in the last decade and present methods of buckling analysis have been used to explain the failures. Experience in the field and laboratory has allowed reductions in factors of safety from about 10 to as low as 1.5 with satisfactory results.